﻿Paul's Ethic of Acceptance: An Exegetical Study of Romans 14:1 - Baker, Kenneth Alan (My University, 1993)
One of the major issues which continues to receive attention in New Testament studies is the debate over the occasion and purpose of Romans. The present exegetical study enters into the "Romans Debate" by focusing on the text of Romans 14:1. It is our thesis that here Paul appeals to the predominantly Gentile Christian "strong" ones in Rome to exercise vigorous acceptance of the predominantly Jewish Christian "weak in faith" who, although sharing in the righteousness of God in Christ, continue to exhibit scruples about food and calendar laws. Our study contributes to the current debate by confirming the plausibility of a concrete situation in Rome which warranted the address of this text. We also demonstrate how our interpretation harmonizes with the major themes of the letter, which are clearly concerned with the relationship between Jew and Gentile in the redemptive historical moment inaugurated by God's action in Christ. By establishing the existence of a significant dimension of Jewish-Gentile relations in Rome, we enable a clearer understanding of Paul's motivation for writing not only the text in question, and the pericope which it introduces, but the entire letter.
Keywords: New Testament, occasion, purpose, Romans, exegetical, hristain, faith